Comunicação e indústria audiovisual : crime, compensação simbólica e outras questões sobre as séries policiais televisivas - Furuzawa, Camila Prado (2014)
This dissertation aims contemporary TV crime drama series, specially the ones with origin in USA, in order to analyze and verify how this audiovisual product, that presents its content in matters that underlie the understanding of justice, among other topics that concern society, fits a commercial interest television. To do so, this work searches into the very origins of the detective genre in literature, film and television, highlighting its main characteristics. This research is important, because it enables to see how television has appropriated this genre. After this theoretical exploration, it will be produced a complete mapping of which TV crime dramas are available in brazilian TV (broadcast and cable/satellite) to understand how the police series are placed in the channel programming, and finally an analysis of police narrative and its features, exploring the topics covered in the series and correlating marketing and sociological aspects of this genre.